PENERAPAN PENDIDIKAN KARAKTER PERSPEKTIF ISLAM PADA GEN Z DI ERA GLOBALISASI - Ardiansyah, Andri; Nisa, Khairun; Amrin, Amrin (Ibn Khaldun University, Bogor, 2023)
Various moral and ethical issues in Generation Z are still significant issues that hinder the progress of a nation's education, with the various characteristics possessed by the current generation, building character education is a very important requirement inIndonesia which really needs to be maintained and developed from Age after age. Departing from that, this research was conducted with the aim of providing an understanding of the application of good character education according to an Islamic perspective in the current era of globalization and rapid technology. This study uses a qualitative approach with observation methods and literature from documents and facts that already existed. The results can be concluded that in the current era of Generation Z it is not only intelligence and (cognitive) skills that can form the next generation of the nation, but with the application of the Islamic Perspective Character Education (Affective) method which is very good to make Generation Z have character according to religious values. and principles that can be realized.